miR-224 Regulates the Aggressiveness of Hepatoma Cells Through the IL-6/STAT3/SMAD4 Pathway - An, Fangmei; Wu, Xiongbo; Zhang, Yunan; Chen, Dayang; Lin, Yexin; Wu, Fang; Ding, Junli; Xia, Min; Zhan, Qiang (Turkish Journal of Gastroenterology, 2021)
Background: Previous studies have shown that miR-224 regulates the progression of liver cancer. The aim of this study was to investigate the underlying mechanisms. Methods: The miR-224, p-STAT3 and SMAD4 expression levels were checked with tissue or/and serum samples of HCC patients by qRT-PCR or IHC methods. The regulatory role of IL-6 in p-STAT3 and SMAD4 was investigated by Western-blot. The targeted gene of miR-224 was verified by both Western-blot and luciferase reporter assay. Furthermore, the carcinogenesis of miR-224 in HCC was investigated by cell experiments in vitro and mouse xenograft model and in vivo imaging in vivo. Results: It was found miR-224 was elevated in both tissue and serum of HCC patients. The p-STAT3 expression was higher but the SMAD4 was lower in the HCC tumor tissues. Moreover, IL-6 can induce the p-STAT3/STAT3 and miR-224 expression in HCC cells and STAT3 played the bridge role between IL-6 and miR-224. Target gene studies found miR-224 targeted the 3ʹUTR of SMAD4. Finally, the promoting roles of miR-224in the growth, proliferation, invasion and migration of HCC were discovered by in vitro and in vivo studies. Conclusion: It implies that miR-224 may potentially represent a new target for developing novel anti-HCC therapeutics.